The Internationalization Process of Small and Medium Companies: the Itlas&LaborLegno Case Study - Dei Tos, Sarah (2010)
Small and medium companies’ presence in the international marketplace is consistently increasing in the last decades, arising the interest of several authors and researchers. The existing internationalization literature can be mainly divided into two main fields, the International Business and International Entrepreneurship one. Nonetheless, neither of them alone is able to fully describe the principal factors determining SMEs internationalization’s strategy and performance in the foreign countries.